How Public Figures Use Language to Inspire: A Pragmatic Analysis of TED Talks by Book Writers and Its Implications for Effective Public Speaking Skills in the Digital Age - Anabella Nuryafitri; Otong Setiawan Djuharie (Jurnal Ilmiah Literasi Indonesia, 2026)
This study examines how public figures who are primarily known as book authors use language pragmatically to inspire audiences in their TED Talks, and what implications these strategies hold for public speaking instruction in the digital age. Employing a qualitative descriptive design, the study analyzes the transcripts of five widely circulated TED Talks delivered by book writers: Brené Brown's "The Power of Vulnerability," Elizabeth Gilbert's "Your Elusive Creative Genius," Susan Cain's "The Power of Introverts," Chimamanda Ngozi Adichie's "The Danger of a Single Story," and Simon Sinek's "How Great Leaders Inspire Action." The utterances were segmented and coded using Searle's (1976) taxonomy of speech acts, Grice's (1975) Cooperative Principle, and a deictic-marker analysis of person and temporal deixis. Findings show that assertive and directive speech acts jointly account for the majority of coded utterances, that speakers strategically flout the maxims of quantity and relation through extended personal narrative before returning to their communicative point, and that inclusive person deixis ("we," "you") is used at a markedly higher rate than exclusive or distancing forms to build audience solidarity. These pragmatic patterns are then discussed in relation to the demands of digital-age public communication, where short attention spans, algorithm-driven platforms, and parasocial audience relationships require speakers to establish relevance and credibility within the opening seconds of a talk. The study concludes with practical implications for public speaking pedagogy, including the deliberate teaching of narrative-led openings, strategic maxim flouting, and inclusive deixis as trainable pragmatic competencies.